The Colonial Java Town and Beach: Chronotopical Analysis of Augusta de Wit’s Two Travelogue Chapters - Sankhyasti, Benedicta Azima; Mulatsih, Maria Vincentia Eka (Journal of Language and Literature, 2024)
When the twentieth century was around the corner, the plurality of residents and newcomers grew in numbers, forming a dynamic and heterogeneous urban society in colonial Java. Augusta de Wit was one of the Dutch authors who wrote about Java during her stay there in her book form travelogue titled Java: Facts and Fancies. Her experience in Java had left an influence on her, which is shown in her fiction works. One of them is the short story Vijandschap that portrays mostly the rural and idyllic life of a coastal community, yet includes the participation of the town (Batavia) as a commercially promising place. This qualitative study aspires to illuminate how the rural beach community reconciled with the town and to confirm what she means by natural beauty by focusing on two chapters “The Town" and “On the Beach.” It is conducted by employing a close reading method and Torop’s chronotopical analysis consisting of topographical, psychological, and metaphysical chronotopes in Augusta de Wit’s perspective while considering the notion of tropicality. This study discovers that there is a relational function of town as a dynamic marketplace to the local folks on the beach and a “space of home” for the Europeans, while the beach as fruitful home to the native beach community and a soothing recreational place to de Wit. Moreover, natural beauty is not confined to nature solely, but includes the locals alongside their character and habits, who are an intrinsic tropical part of Java.